Wavelet Galerkin method for solving singular integral equations - Maleknejad, K; Nosrati, M; Najafi, E (Computational & applied mathematics, 2012)
An effective technique upon linear B-spline wavelets has been developed for solving weakly singular Fredholm integral equations. Properties of these wavelets and some operational matrices are first presented. These properties are then used to reduce the computation of integral equations to some algebraic equations. The method is computationally attractive, and applications are demonstrated through illustrative examples. Mathematical subject classification: 45A05, 32A55, 34A25, 65T60.